2001
DOI: 10.1046/j.1468-3083.2001.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in trichothiodystrophy

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…518,[528][529][530][531][532] This results from a deficiency of the sulfur-containing aminoacid cystine in the cuticle and cortex. 518,[528][529][530][531][532] This results from a deficiency of the sulfur-containing aminoacid cystine in the cuticle and cortex.…”
Section: Trichorrhexis Nodosamentioning
confidence: 99%
“…518,[528][529][530][531][532] This results from a deficiency of the sulfur-containing aminoacid cystine in the cuticle and cortex. 518,[528][529][530][531][532] This results from a deficiency of the sulfur-containing aminoacid cystine in the cuticle and cortex.…”
Section: Trichorrhexis Nodosamentioning
confidence: 99%
“…32 The X-ray analysis results also showed that calcium was absent in tracts corresponding to dark bands, whereas it was normally present in light bands. 39 Amino-acid analysis of hair in trichothiodystrophy shows notably low cysteine content (less then half of normal content), that parallels the low total sulfur content. 38 Light microscopy showed hair shafts with an irregular, undulating contour and clean transverse fractures through the hair shaft (trichoschisis).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The deficiency of sulphur in the skin and its appendages causes brittle, dry and sparse body hair with a typical pattern of alternating light and dark bands ('tiger-tail banding') on polarized light microscopy. [3][4][5][6] Newborns frequently present with a collodion membrane, followed by ichthyosis of the skin and nail deformities like brittleness, koilonychia and onychoschizia. Additional important features of TTD include pregnancy and birth complications, growth restriction, neurological impairment, gonadal dysgenesis, haematological and ophthalmological abnormalities and recurrent life-threatening infections.…”
Section: Introductionmentioning
confidence: 99%
“…in 1979, is an uncommon autosomal recessive syndrome which is characterized by a variety of skin, hair and nail anomalies . The deficiency of sulphur in the skin and its appendages causes brittle, dry and sparse body hair with a typical pattern of alternating light and dark bands (‘tiger‐tail banding’) on polarized light microscopy . Newborns frequently present with a collodion membrane, followed by ichthyosis of the skin and nail deformities like brittleness, koilonychia and onychoschizia.…”
Section: Introductionmentioning
confidence: 99%